Transformasi Kelembagaan Petani menjadi Badan Usaha Milik Petani (BUMP): Studi Kasus di BUMP PT. Pengayom Tani Sejagad Wonogiri - Amalia Nadifta Ulfa; Widiyanto Widiyanto; Indah Nurhidayati; Putri Permatasari; Haryani Saptaningtyas (Universitas Halu Oleo, 2021)
BUMP is an agribusiness institutional innovation that aims to empower farmers and increase the economic benefits of farmers through farming. Changes in the form of farmer associations to BUMP certainly cannot be separated from problems, therefore research on the transformation of farmer institutions to BUMP is needed to find institutional development models. This study aims to analyze the institutional model and the development of institutional transformation into BUMP at BUMP PT Pengayom Tani Sejagad. This study uses a qualitative approach with a descriptive method. The research location was carried out at BUMP Pengayom Tani Sejagad which is located in Wonogiri Regency. Determination of the research location is done purposively. The method of determining the informants was done by purposive sampling. Sources of data used include primary data and secondary data. Data collection techniques were carried out in several ways, including: in-depth interview, observation, Focus Group Discussion (FGD), recording and documentation. The data analysis technique uses the Miles and Huberman interactive analysis model. The form of corporation in PT. Pengayom Tani Sejagad is a limited company. Activities carried out by BUMP PT. Pengayom Tani Sejagad in the context of agribusiness includes organic farming business activities that covers on-farm to off-farm. BUMP PT. Pengayom Tani Sejagad plays a role in terms of organizational management and farm business management that supports the goal of protecting and empowering farmers.Keywords: transformation; institutional; farmers; BUMP